How comparable are species distributions along elevational and latitudinal climate gradients?. Issue 11 (3rd July 2013) - Halbritter, Aud H.; Alexander, Jake M.; Edwards, Peter J.; Billeter, Regula
Abstract: Aim: Because climatic factors, especially temperature, show similar trends with elevation and latitude, it is often assumed that elevational gradients can be used as a proxy for understanding ecological processes along latitudinal gradients. We investigated the validity of this assumption for herbaceous plants, testing the hypotheses that (1) species reach the same climate limits, and (2) exhibit similar distribution patterns along both types of gradient. Location: Swiss Alps and Scandinavia. Methods: We recorded the occurrence of 155 ruderal plant species along an elevational gradient in the Swiss Alps and a latitudinal gradient, both reaching beyond the distribution limit of most species. Principal components analysis was used to summarize climatic variation in temperature and precipitation across these gradients and assessed the relationship across species between climatic limits along the two gradients. We used logistic regressions to compare how the probability of occurrence of individual species changed with climate along the two gradients. Results: We found no correlation of species principal components analysis (PCA) values (climate limit) along an elevational and latitudinal precipitation gradient (PC1) but a positive correlation along a temperature gradient (PC2). Species reached a colder climate limit (on average 244 growing degree days lower) and decreased in occurrence more gradually along the elevational compared to the latitudinal gradient. Main conclusions: We suggest that the differences in distribution patterns and limits along similar climatic gradients are mainly due to the much shorter dispersal distances along elevational than latitudinal gradients, although other explanations are also possible. We can therefore expect plants in mountains and lowland regions to respond differently to rapid climate change, and so caution must be exercised when using elevation as a proxy for latitude in studies of species distribution. Nonetheless, comparative studies along such gradients can yield important insights into the factors that limit species distributions.